Be-Breeder - Learning: a new tool for teaching and learning plant breeding principles - Fritsche-Neto,Roberto (2016)
Abstract The Be-Breeder application is an on-line tool constructed through the R software for the purpose of assisting in some of the main genetic and statistical analyses related to the area of plant breeding. In addition, Be-Breeder provides a section called "Learning", which in a simple click-point manner allows explanation of theories related to the effect of inbreeding, population structure, qualitative and quantitative traits, heterosis, population size, effect of selection, and composition of hybrids. Be-Breeder is available for network use on the website of the Allogamous Plant Breeding Laboratory (Laboratório de Melhoramento de Plantas Alógamas) of ESALQ-USP through the link: http://www.genetica.esalq.usp.br/alogamas/R.html.